2021
DOI: 10.1098/rsif.2020.0900
|View full text |Cite
|
Sign up to set email alerts
|

Fibril density reduction in keratoconic corneas

Abstract: This study aims to estimate the reduction in collagen fibril density within the central 6 mm radius of keratoconic corneas through the processing of microstructure and videokeratography data. Collagen fibril distribution maps and topography maps were obtained for seven keratoconic and six healthy corneas, and topographic features were assessed to detect and calculate the area of the cone in each keratoconic eye. The reduction in collagen fibril density within the cone area was estimated with reference to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In addition, knowing the transmittance of the normal corneal layers can help us to know the influence of ultraviolet absorption in patients with certain corneal pathologies or after some surgical procedures. For instance, corneal diseases such as keratoconus, which may result in a progressive thinning of the corneal and cells composition [ 18 ], might affect corneal spectral transmission, and it would be important to protect the cornea, the lens, and the retina from the UV radiation that would normally be blocked by a healthy cornea.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, knowing the transmittance of the normal corneal layers can help us to know the influence of ultraviolet absorption in patients with certain corneal pathologies or after some surgical procedures. For instance, corneal diseases such as keratoconus, which may result in a progressive thinning of the corneal and cells composition [ 18 ], might affect corneal spectral transmission, and it would be important to protect the cornea, the lens, and the retina from the UV radiation that would normally be blocked by a healthy cornea.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with ex vivo experimental results using electron microscopy and x-ray scattering in which the collagen fibrils’ organisation was significantly altered inside the keratoconic KC area of pathology but remained unaffected outside it ( Radner et al, 1998 ; Meek et al, 2005 ). Using x-ray scattering, Zhou et al observed that the magnitude of collagen fibril density reduction inside the cone area was up to 35% in advanced KC cases ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the validation of the mapping method relied on comparing the numerically-predicted, SSI-based deformation of the cornea along only the cornea’s principal temporal-nasal meridian to that measured clinically by the Corvis ST ( Zhang et al, 2021 ). Further, the method to relate the fibril density reduction inside the cone with the cone morphology was based on information obtained from only 7 KC corneas ( Zhou et al, 2021 ). On the clinical side, it is important to note that the relatively small sample used in the study and the lack of cases in which there was a small progression extent represented other limitations, which will be addressed in prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior lamellae also exhibit thinning, splitting, and distortion along with Vogt’s striae, which run anteriorly from the deep posterior stroma: while normal corneas also have these striae, they are more numerous and longer in keratoconus. Other notable changes in keratoconus are thinning and fragmentation of Bowman’s membrane, thickening of the epithelial layer to fill the void left by the shrunken stroma, and in end-stage disease, rupture of Descemet’s membrane and the onset of hydrops [ 3 , 6 , 12 , 13 , 17 23 ]. These changes are all largely concentrated in the region where the cone forms ( Fig 1D ).…”
Section: Introductionmentioning
confidence: 99%